2017
DOI: 10.1089/aivt.2016.0024
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Using RNA Sequencing Profiling in a Reconstituted Airway Epithelium Exposed to Conventional Cigarette Smoke or Electronic Cigarette Aerosols

Abstract: The use of electronic cigarettes (e-cigarettes) potentially offers a safer alternative to conventional tobacco products. The advance in molecular biology and computational sciences offers new perspective to assess adverse biological responses for product risk assessment by combining omics screens with knowledge-based biological pathways. Our aim was to compare transcriptomic perturbations in MucilAirÔ, a commercially available lung epithelial tissue, after short repeated exposure to cigarette smoke (3R4F) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…We also had previously reported that the pattern of gene expression changes was comparable between cultures from two donors following CS exposure [35]. Furthermore, Banerjee et al reported that a similar trend of inflammatory mediator secretion was detected in cultures from six different donors following CS exposure [50]. These studies thus support that the results of the present study, despite using data from one donor, can still provide valuable insights into the underlying mechanisms associated with CS and EC aerosol exposures.…”
Section: Discussionmentioning
confidence: 54%
“…We also had previously reported that the pattern of gene expression changes was comparable between cultures from two donors following CS exposure [35]. Furthermore, Banerjee et al reported that a similar trend of inflammatory mediator secretion was detected in cultures from six different donors following CS exposure [50]. These studies thus support that the results of the present study, despite using data from one donor, can still provide valuable insights into the underlying mechanisms associated with CS and EC aerosol exposures.…”
Section: Discussionmentioning
confidence: 54%
“…We observed CYP1A1 induction between 1348- and 876-fold at pFDR < 0.01 at 24 hrs and 48 hrs, respectively. We also previously reported CYP1A1 induction by cigarette smoke in MucilAir™ in shorter exposure runs 24 . Finally, for the e-cigarette aerosol treatment, only FGF14 and EGR1 were significant in the qPCR at p < 0.05, FC > [1.5] at the 1/7 aerosol dilution (Supplementary Table S21 , Fig.…”
Section: Resultsmentioning
confidence: 60%
“…We were able to follow fusion and fission events characteristic of protein liquid droplets (not shown). 41 We suggest that 1% (v/v) dimethyl sulfoxide (DMSO), which is the SYPRO orange vehicle, can result in this non-equilibrium state depicted by vacuolized droplets possessing varying densities. To provide insights into the structure of the rPrP 90-231 phase-separated state, we added SYPRO orange, a dye that only exhibits fluorescence when bound to hydrophobic surfaces exposed to solvent.…”
Section: The C-terminal Globular Domain Of Rprp Phase Separates In mentioning
confidence: 99%